Molo.news: Experimentally Developing a Relational Platform for Local Journalism - Hepp, Andreas (2019)
In this article we present a research project that experimentally develops a local news platform based on empirical research (interviews, group discussions, a survey) and a co-creation approach. What is presented here is not a typical empirical social science research study but the culmination of an entire approach that is oriented toward software development. This article’s aim is to present the project’s conceptual ideas, its interdisciplinary character, its research-based development approach and the concept for a local news platform that grew out of our preliminary work. At each level we focus on the relationality which arises in the figurations of the actors involved and their various perspectives. First, we illustrate how relationality already shaped the objective of our project and how this results in its interdisciplinary structure and research design. We then discuss this idea with reference to our empirical findings, that is, the paradox of the local public sphere: While all the actors we interviewed—those who (professionally) produce content and those who use it—have a high appreciation for the idea of a local public sphere, the mediated connection to this sphere is diminishing at the same time. We understand this as the real challenge for local journalism and the local public sphere at large, and not just for individual media organizations. This is also the reason why we argue for a fundamentally relational approach: from a theoretical point of view, it can be used to grasp the crisis of the local public; from a practical point of view, relationality represents the core characteristic of the platform in development. On this basis, we will then show how the concept of the experimental local news platform evolved through the use of a prototype as a relational boundary object. This development lead to the conceptualization of the platform molo.news which itself is characterized by a fourfold relationality. Our concluding argument is that approaching relationality in a more rigorous way could be the key to exploring the future of local journalism.